The Relevance of the Una Via Principle in the Enforcement of Election Criminal Law in Indonesia in Case Number 233/Pid.Sus/2024/PT Mam at the West Sulawesi High Court - Slamet Suwaryo; Soediro; Indriati Amarini; Selamat Widodo (Talenta Publisher, 2026)
This research aims to determine the relevance of handling violations of the Election Law through the application of the Una Via Principle in the decision of the West Sulawesi High Court in case number 233/Pid.Sus/2024/PT.Mam, as well as to examine the relevance of the Una Via Principle in the enforcement of election criminal law in Indonesia. This research is normative legal research; therefore, the materials examined are library materials or secondary data obtained through literature study. The data that have been obtained are then analyzed qualitatively, so that the data are presented in a descriptive-prescriptive manner, and the method of drawing conclusions is carried out deductively. This research reaches two conclusions. First, in Decision Number 233/Pid.Sus/2024/PT Mam, the Una Via Principle is highly relevant to be applied because, although administrative sanctions are formally not criminal in nature, substantively they produce a second punitive effect (quasi punitive effect). This inconsistency directly undermines the principles of proportionality and legal certainty (Article 28D paragraph 1 of the 1945 Constitution). Through this reconstruction, election law enforcement is no longer sectoral in nature, but becomes an integrated system based on the Una Via Principle in order to guarantee legal certainty, justice, and the effectiveness of handling campaign violations. Second, the Una Via Principle is relevant because it is able to overcome the problem of fragmented authority, which has long been a major obstacle in election law enforcement. Through this principle, every campaign violation is processed within one coordinated handling pathway, thereby avoiding overlapping authority and accelerating case resolution, as well as preventing excessive punishment.